2015
DOI: 10.1177/0165025415576816
|View full text |Cite
|
Sign up to set email alerts
|

Infant frontal asymmetry predicts child emotional availability

Abstract: While factors influencing maternal emotional availability (EA) have been well investigated, little is known about the development of child EA. The present longitudinal study investigated the role of frontal brain asymmetry in young children with regard to child EA (child responsiveness and involvement) in mother-child interaction in a sample of 28 children at 7, 14, and 50 months of age. When infants were 7 months of age, mother-child interaction quality was assessed using the EA-Scales. At 14 months, infants'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 33 publications
1
18
1
Order By: Relevance
“…Our findings are in line with previous research demonstrating the relationship between approach‐oriented emotions, approach motivation, and approach‐related constructs with increased left frontal cortical activity (e.g., Davidson & Fox, ; Fox, ; Fox et al, ; Harmon‐Jones et al, ; Licata et al, ; Pizzagalli et al, ; Shankman et al, , ; Sutton & Davidson, ; Tomarken & Keener, ). In addition, a personality trait related to a stronger approach tendency, the BAS (Gray, ), is linked to an increase in relative left frontal alpha activity after a difficult decision is made (Harmon‐Jones et al, ; Harmon‐Jones et al, ).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings are in line with previous research demonstrating the relationship between approach‐oriented emotions, approach motivation, and approach‐related constructs with increased left frontal cortical activity (e.g., Davidson & Fox, ; Fox, ; Fox et al, ; Harmon‐Jones et al, ; Licata et al, ; Pizzagalli et al, ; Shankman et al, , ; Sutton & Davidson, ; Tomarken & Keener, ). In addition, a personality trait related to a stronger approach tendency, the BAS (Gray, ), is linked to an increase in relative left frontal alpha activity after a difficult decision is made (Harmon‐Jones et al, ; Harmon‐Jones et al, ).…”
Section: Resultssupporting
confidence: 92%
“…Thereby, greater right relative to left frontal activity has been linked to withdrawal‐oriented emotions, to an avoidance motivation, and to the experience of negative affect (e.g., Davidson, Ekman, Saron, Senulis, & Friesen, ; Fox, ; Fox, Henderson, Rubin, Calkins, & Schmidt, ; Harmon‐Jones, Gable, & Peterson, ; Jones & Fox, ; Saby & Marshall, ; Shankman et al, , ; Sutton & Davidson, ). Furthermore, greater relative left frontal activity has been associated with approach‐oriented emotions, to an approach motivation, and the experience of positive affect (e.g., Davidson & Fox, ; Fox, ; Fox et al, ; Harmon‐Jones et al, ; Licata, Paulus, Kühn‐Popp, Meinhardt, & Sodian, ; Paulus, Kühn‐Popp, Licata, Sodian, & Meinhardt, ; Pizzagalli, Sherwood, Henriques, & Davidson, ; Shankman et al, , ; Sutton & Davidson, ; Tomarken & Keener, ). For example, video clips that evoke fear or disgust resulted in greater relative right frontal brain activity (Davidson et al, ; Jones & Fox, ), while 10‐month‐old infants displayed increased left frontal activation after watching film clips of a woman with a happy facial expression as compared with a sad expression (Davidson & Fox, ).…”
mentioning
confidence: 99%
“…Insecure-preoccupied subjects tend to hyper-activate the attachment system and report about childhood experiences eliciting highly intense emotions. Indeed, left frontal hemisphere activation is associated with approach-related motivation, coping and proactive social behavior (Davidson, 1992; Master et al, 2009; Licata et al, 2015). However, relatively increased LFA has also been found in dispositional anger which can be regarded an approach related tendency as well (Harmon-Jones and Allen, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation of this study is that the design does not allow to draw upon assumptions on the causal mechanisms between neural measures and emotion regulation strategies associated with different attachment representations. While associations between frontal asymmetry and attachment as well as maternal depressive symptoms have already been found in young children (e.g., Field et al, 1995; Dawson et al, 1997; Dawson et al, 2001), a recent study’s findings suggest that frontal hemispheric asymmetry may be less influenced by environmental factors (Licata et al, 2015). It would be very interesting to apply a longitudinal approach to attachment related emotion regulation strategies and the neural circuits that are associated with the phenomenon beyond childhood.…”
Section: Limitationsmentioning
confidence: 90%
“…Thus, we argue that adult sensitivity is not the only factor that contributes to the relationship’s health. Interestingly, a recent study by Licata et al (2015) found that child involvement was related to maternal sensitivity and higher left frontal activation of the brain, as measured with the electroencephalogram. However, child responsiveness was related to maternal sensitivity, but not neurological activation.…”
Section: Emotional Availabilitymentioning
confidence: 99%